Auditor Credibility and Initial Public Offerings. - Menon, Krishnagopal; Williams, David D. (The Accounting Review, 1991)
An important differentiating attribute of the audit product is believed to be the credibility that the auditor is perceived to bring to an audit engagement. This study uses the context of the initial public offering (IPO) to investigate auditor credibility. It is contended that information asymmetry problems lead to a demand for credible auditors in companies going public. Entrepreneurs have incentives to signal their knowledge of favorable future earnings by selecting reputable auditors. Since there is limited information available on firms going public, employing credible auditors can convey monitoring cost advantages as well. Investment bankers also have a preference for credible auditors since they rely on audited financial statements in certifying the value of the firm and determining whether to underwrite the offering. In the present study, we consider auditor credibility in IPOs from the perspective of the client and the investment banker. If there is an increased demand for auditor credibility at the time of the IPO, there should be a significant number of credibility-increasing auditor changes prior to the offering. Further, if the investment banker benefits from having a more credible auditor sign off on statements prepared by the client, this should be reflected in the investment banker's fee structure. The empirical analysis is performed on companies that went public in 1985 and 1986. Relatively few auditor changes are observed prior to the offering. However, among those companies making auditor changes, there is a clear preference for more credible auditors. Logistic regression analysis shows that companies with prestigious investment bankers are more likely to change away from local auditors to more credible CPAs. The type of underwriting arrangement employed is also significant, consistent with an investment banker preference for credible auditors. A regression analysis is conducted, using the 1985 and 1986 IPOs, modeling investment banker compensation as a function of several factors, including type of auditor employed by the issuing firm. In the case of "firm commitment" offerings, the auditor type is found to be significant. Clients seem to be charged a smaller investment banking fee if they are associated with Big Eight auditors. There is no apparent auditor effect in the case of "best efforts" offerings. The evidence generally supports the hypothesis that investment bankers and their clients have a preference for credible auditors for the IPO.